Analysis of the directions of development of digital aesthetics on the example of Windows interfaces - Maksymilian Cegiełka; Miłosz, Marek (Journal of Computer Sciences Institute, 2025)
The analysis of digital aesthetics in Windows systems was undertaken due to an observable trend over the past decade toward the gradual simplification and even marginalization of interface visual appeal. The aim is to demonstrate that the peak of usability, accessibility, and quality was reached at the end of the first decade of the 21st century and the beginning of the second – during a period when a humanistic trend in interface design, now referred to as Aero, prevailed. This aesthetic will be compared with other trends, surveys will be conducted, and credible sources will be cited. One of the main objectives of this study is to raise awareness of this topic and emphasize the need for change.